Confocal Raman microscopy for assessing effects of preservation methods on symbiotic deep-sea mussel gills - He, Wanying; Wang, Minxiao; Li, Mengna; Zhong, Zhaoshan; Chen, Hao; Xi, Shichuan; Luan, Zhendong; Li, Chaolun; Zhang, Xin (Frontiers in Marine Science, 2022)
Confocal Raman microscopy (CRM) is a powerful tool for biological research, which can provide information regarding the composition and distribution of biomolecules in an in situ, label-free, non-destructive manner and with high spatial resolution. Sample preservation is often an unavoidable step, especially for non-model organisms in the field. Moreover, protocols for the preservation of samples for CRM have not been established. Deep-sea mussel Gigantidas platifrons has characteristics of non-model organisms. In this study, we used Gigantidas platifrons as the study model and investigated the effect of four common preservation methods on the results of CRM imaging and signals. The methods included snap-freeze (CS), snap-freeze followed by rapid fixation in methanol (CS-MeOH), 2.5% glutaraldehyde and 2% paraformaldehyde fixation (CS-GP), and 4% paraformaldehyde and alcohol fixation (PS-PA). The results of this study indicate that CS was the most effective method for the comprehensive analysis of the biomolecular composition although the sectioning success rate was relatively low. Moreover, CS-MeOH was found to be effective when CS is not sufficient in obtaining good morphology in sections, or when the effect of chemical bonding on the composition of biomolecules upon CS-MeOH can be neglected. Finally, CS-GP and PS-PA were found to be the most effective methods considering the overall morphological observation. However, they were less suitable for metabolic studies. We believe our results can provide guidance for further studies of Raman on non-model biological samples. It is of great importance for the wide application of Raman technique.